Metabolites Profiling and In Vitro Biological Characterization of Different Fractions of Cliona sp. Marine Sponge from the Red Sea Egypt - Wafaa H. B. Hassan; Zeinab I. El Sayed; Lamya H. Al-Wahaibi; Mahmoud M. Abdel-Aal; Wael M. Abdel-Mageed; Eman Abdelsalam; Sahar Abdelaziz (Molecules, 2023)
Red Sea marine sponges are an important source of biologically active natural products. Therefore, the present study aimed to investigate, for the first time, the components of n-hexane, dichloromethane, and ethyl acetate fractions of Cliona sp. marine sponge collected from the Red Sea, Egypt using UPLC-ESI-MS/MS (Ultra-performance liquid chromatography electrospray ionization tandem mass spectrometry) analysis. The analysis revealed the tentative identification of 23, 16, and 24 compounds from the n-hexane, dichloromethane, and ethyl acetate fractions of Cliona sp., respectively. In addition, the examination of these fractions resulted in the isolation and identification of three sterols and one amino acid. The identification of the isolated compounds was confirmed by 1D and 2D NMR (Nuclear Magnetic Resonance), and MS (Mass spectrometry), and IR (Infrared) spectroscopy. The in vitro cytotoxic, antioxidant, and antimicrobial activities of the total ethanolic extract and its sub-fractions were also evaluated. Interestingly, the ethyl acetate fraction showed potent cytotoxic activity against colon (HCT-116) and human larynx carcinoma (HEP-2) cell lines with IC50 (Half-maximal Inhibitory Concentration) 6.11 ± 0.2 and 12.6 ± 0.9 µg/mL, respectively. However, the dichloromethane fraction showed strong antioxidant activity, with IC50 75.53 ± 3.41 µg/mL. Notably, the total ethanolic extract showed the strongest antibacterial activity against Staphylococcus aureus and Escherichia coli, with MIC (Minimum Inhibitory Concentration) 62.5 ± 0.82 and 125 ± 0.62 µg/mL, respectively, compared to other fractions. In conclusion, this is the first report on the secondary metabolites content and biological activities of Cliona sp. from the Red Sea, Egypt. It also highlights the need for further research on the most active fractions against various cancer cell lines and resistant bacterial and fungal strains. Cliona sp. extract and its fractions could be a potential source of novel and safe natural drugs with a wide range of medicinal and pharmaceutical applications.